Estimating Black Hole Masses in Obscured Active Galactic Nuclei from X-Ray and Optical Emission Line Luminosities - Stephanie LaMassa; Isabella Farrow; C. Megan Urry; Benny Trakhtenbrot; Connor Auge; Michael J. Koss; Alessandro Peca; Dave Sanders; Tracey Jane Turner (The Astrophysical Journal)
We test a novel method for estimating black hole masses ( M _BH ) in obscured active galactic nuclei (AGN) that uses proxies to measure the FWHM of broad H α (FWHM _bH _α ) and the accretion disk luminosity at 5100 Å ( λL _5100 Å ). Using a published correlation, we estimate FWHM _bH _α from the narrow optical emission line ratio L _[O _iii _] / L _nH _β . Using a sample of 99 local obscured AGN from the Swift Burst Alert Telescope AGN Spectroscopic Survey (BASS), we assess the agreement between estimating λL _5100 Å from the intrinsic 2 to 10 keV X-ray luminosity and from narrow optical emission lines. We find a mean offset of 0.32 ± 0.68 dex between these methods, which propagates to a factor of ∼2 uncertainty when estimating M _BH using a virial mass formula where L _[O _iii _] / L _nH _β serves as a proxy of FWHM _bH _α ( M _BH,[O _iii _]/nH _β ). We compare M _BH,[O _iii _]/nH _β with virial M _BH measurements from broad Paschen emission lines. For the 14 (12) BASS AGN with broad Pa α (Pa β ) detections, we find M _BH,[O _iii _]/nH _β to be systematically higher than M _BH,Pa _α ( M _BH,Pa _β ) by a factor of 0.39 ± 0.44 dex (0.48 ± 0.51 dex). Since these offsets are within the scatter, more data are needed to assess whether M _BH,[O _iii _]/nH _β is biased high. For 151 BASS AGN with measured stellar velocity dispersions ( σ _* ), we find that the σ _* -derived M _BH agrees with M _BH,[O _iii _]/nH _β to within 0.08 dex, albeit with wide scatter (0.74 dex). The method tested here can provide estimates of M _BH in thousands of obscured AGN in spectroscopic surveys when other diagnostics are not available, though with an uncertainty of ∼3–5.